Free-Living Enterobacterium Pragia fontium 24613: Complete Genome Sequence and Metabolic Profiling - Snopková, Kateřina; Sedlář, Karel; Bosák, Juraj; Chaloupková, Eva; Sedláček, Ivo; Provazník, Valentýna; Šmajs, David (SAGE Publishing, 2017)
Pragia fontium is one of the few species that belongs to the group of atypical hydrogen sulfide-producing enterobacteria. Unlike other members of this closely related group, P. fontium is not associated with any known host and has been reported as a free-living bacterium. Whole genome sequencing and metabolic fingerprinting confirmed the phylogenetic position of P. fontium inside the group of atypical H2S producers. Genomic data have revealed that P. fontium 24613 has limited pathogenic potential, although there are signs of genome decay. Although the lack of specific virulence factors and no association with a host species suggest a free-living style, the signs of genome decay suggest a process of adaptation to an as-yet-unknown host.

Pragia fontium is one of the few species that belongs to the group of atypical hydrogen sulfide-producing enterobacteria. Unlike other members of this closely related group, P. fontium is not associated with any known host and has been reported as a free-living bacterium. Whole genome sequencing and metabolic fingerprinting confirmed the phylogenetic position of P. fontium inside the group of atypical H2S producers. Genomic data have revealed that P. fontium 24613 has limited pathogenic potential, although there are signs of genome decay. Although the lack of specific virulence factors and no association with a host species suggest a free-living style, the signs of genome decay suggest a process of adaptation to an as-yet-unknown host.
Free-Living Enterobacterium Pragia fontium 24613: Complete Genome Sequence and Metabolic Profiling
Keywords: Pragia fontium; Enterobacteriaceae; whole genome sequence; phylogeny; free-living bacteria; Pragia fontium; Enterobacteriaceae; whole genome sequence; phylogeny; free-living bacteria